LATEST COMPUTER TECHNOLOGIES - ON HELPING FUTURE MUSIC TEACHERS - L.I. Varnavska (Academy of Cognitive and Natural Sciences, 2007)
The article discusses the need and some questions about arranging music in ways computer technologies by future music teachers.